The Potential of Laserpuncture Technology and Probiotics on Weight and Digestibility Crude Protein of Madura Bull at Tlagah Village, Sampang-East Java - Muhammad Ahdi Kurniawan; Lucia Tri Suwanti; Mufasirin Mufasirin; R. Tatang Santanu Adikara; Soeharsono Soeharsono; Sunaryo Hadi Warsito; Hana Eliyani; Wahidan Qodiip Maulana (Journal of Applied Veterinary Science And Technology, 2023)
Background: Laserpuncture is a technology that uses short-wave rays to receptors (acupuncture points) to increase the capacity and efficiency of organs to increase the productivity of animals’ livestock. This can improve feed efficiency to help breeders maximize their beef bull fattening business. Purpose: This study was to test the potential of laserpuncture and probiotics on body weight gain and the digestibility of crude protein in Madura bull. Methods: This study used 12 Madura bulls with an age range of 2-2.5 years. The bulls were divided into two treatment groups. The P1 group shot laserpuncture at a dose of 0.5 joules. The P2 group received laserpuncture at a dose of 0.5 joules with 5 ml of probiotics administration in 1 liter of water. Data was taken by recording the weight gain of Madurese bulls every week and the results of crude protein digestibility testing. The resulting data is then analyzed using the T-test. Results: This study showed no significant difference between P1 and P2 in male Madura cattle’s body weight gain and crude protein digestibility. Conclusion: The combination of laserpuncture at the growth point and probiotic administration in feed did not cause a significant difference in weight gain or digestibility of crude protein in male Madurese bull.